An objective methodology capturing online commodity marketing and other harms. (27th January 2020) - Vaipuna, Tevita; Allison, Lucy; Bhasin, Abhinav; Choi, Kimberley; Chu, Agnes; Grice, Karl; Hay, Alice; Huang, Stephanie; Jarvis, Ellie-May; Laing, Bridie; Lewis, Alexandra; Moriarty, Ripeka Huitau; et al.
Abstract: Increasingly life is lived online, yet little is known about the actual nature and extent of online content that people view due to the difficulty of recording real time exposure. This includes people's exposure to harmful commodity marketing. This study aimed to develop a methodology to assess the nature and extent of exposure to, and engagement with, unhealthy commodity marketing and other public health harms online, particularly children's exposure. A convenience sample of 16 young adult participants (aged 21–29) recorded their device usage for 2 days using Zoom software. Data were coded and analysed to assess the nature and extent of marketing for alcohol, gambling, junk food and smoking products. Four focus groups were conducted with participants to explore their data collection and coding experiences, and results assessed using thematic analysis. The study found that, with some modifications, this method was feasible for gathering real-time objective data from the online world that can be analysed for a range of public health harms, including marketing of unhealthy commodities. Larger studies are recommended to build global evidence for public health action in the online world.